Transforming growth factor β induced FoxP3+ regulatory T cells suppress Th1 mediated experimental colitis. Issue 5 (14th September 2005) - Fantini, M C; Becker, C; Tubbe, I; Nikolaev, A; Lehr, H A; Galle, P; Neurath, M F
Abstract : Background and aims: The imbalance between effector and regulatory T cells plays a central role in the pathogenesis of inflammatory bowel diseases. In addition to the thymus, CD4+CD25+ regulatory T cells can be induced in the periphery from a population of CD25− T cells by treatment with transforming growth factor β (TGF-β). Here, we analysed the in vivo function of TGF-β induced regulatory T (Ti-Treg) cells in experimental colitis. Methods: Ti-Treg cells were generated in cell culture in the presence or absence of TGF-β and tested for their regulatory potential in experimental colitis using the CD4+CD62L+ T cell transfer model. Results: Ti-Treg cells significantly suppressed Th1 mediated colitis on CD4+CD62L+ T cell transfer in vivo, as shown by high resolution endoscopy, histology, immunohistochemistry, and cytokine analysis. Further analysis of in vivo and in vitro expanded Ti-Treg cells showed that exogenous interleukin 2 (IL-2) was crucial for survival and expansion of these cells. Conclusion: Our data suggest that regulatory Ti-Treg cells expand by TGF-β and exogenous IL-2 derived from effector T cells at the site of inflammation. In addition to Tr1 and thymic CD4+CD25+ T cells, peripheral Ti-Treg cells emerge as a class of regulatory T cells with therapeutic potential in T cell mediated chronic intestinal inflammation.